2003
DOI: 10.1177/009102600303200404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Burnout in the Relationship between Perceptions off Organizational Politics and Turnover Intentions

Abstract: Despite rich evidence suggesting that perceptions of organizational politics are significantly related to turnover intentions, the reasons of the relationship are unexplored. This study aims to determine whether job burnout can serve as a mediator in the relationship between perceptions of organizational politics and turnover intentions and which component of burnout is most effective in mediating this relationship. Moreover, burnout was investigated in a profession outside human services. Multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 5 publications
11
91
0
9
Order By: Relevance
“…Hypothesis one claims for a positive association between burnout and turnover intentions. In line with the results of prior scholarships (Huang, Chuang & Lin, 2003;Rahim & Cosby, 2016;Spence Laschinger et al, 2009), burnout was found positively associated with turnover intentions and workplace incivility. It is due to the fact that burnout is that psychological state in which people become emotionally exhausted and cynic and start evaluating themselves adversely.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hypothesis one claims for a positive association between burnout and turnover intentions. In line with the results of prior scholarships (Huang, Chuang & Lin, 2003;Rahim & Cosby, 2016;Spence Laschinger et al, 2009), burnout was found positively associated with turnover intentions and workplace incivility. It is due to the fact that burnout is that psychological state in which people become emotionally exhausted and cynic and start evaluating themselves adversely.…”
Section: Discussionsupporting
confidence: 86%
“…and other individual characteristics that do not relate to work such as family size, family and spouse responsibilities etc. The theoretical framework of burnout suggested by Demerouti et al, (2001) and findings of Arnold and Feldman (1982) have both been empirically supported by many researchers (Huang et al, 2003;Kim & Stoner, 2008;Rahim & Cosby, 2016). These studies conclude that a positive association exists between burnout and turnover intentions.…”
Section: Burnout Turnover Intentions and Workplace Incivilitymentioning
confidence: 62%
See 1 more Smart Citation
“…그러나 간호영역에서는 이 직의도와 스트레스, 직무만족, 임파워먼트, 조직몰입, 소진 등의 일 부요인 간의 상관관계 (Park & Park, 2008)나 인과관계 연구 (Huang, Chuang, & Lin, 2003;Jeong et al, 2008;Kim, I. W., 2005 …”
unclassified
“…A partir do final dos anos 70, importantes frentes de pesquisa foram iniciadas com o intuito de entender como os funcionários reagiam ao perceber esse ambiente político (e.g., Schein, 1977;Tushman, 1977;Madison, Allen, Porter, Renwick & Mayes, 1980). Em estudos mais recentes constatou-se que a Percepção de Política na Organização (PPO) traz diversos resultados negativos, levando, por exemplo, a queda de desempenho, insatisfação no trabalho, frustração e aumento de turnover (Bedi & Schat, 2013;Huang & Chuang, 2003;Kacmar & Carlson, 1997;Rosen, Harris, & Kacmar, 2009;Vigoda, 2000).…”
Section: Introductionunclassified